PANCASILA AS A DEVELOPMENT PARADIGM IN INDONESIA PANCASILA AND CIVIC EDUCATION - Intan Fajri; Siti Istianah; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2022)
PANCASILA AS A DEVELOPMENT PARADIGM IN INDONESIA PANCASILA AND CIVIC EDUCATION